Risiko Penggunaan Kecerdasan Buatan (AI) dalam Tugas Perkuliahan: Studi Kualitatif Mahasiswa - Pranoto Effendi (Jurnal Teknik Informatika dan Teknologi Informasi, 2024)
The use of AI has become widespread among university students as a tool to improve the efficiency and quality of their studies. While AI aims to support the education system and enhance the learning process, its use, while providing benefits, is also perceived to pose risks. This article aims to uncover the use of AI and its associated risks by exploring perceptions from a student perspective. Qualitative methods were used with 53 student respondents, asking open-ended questions regarding AI use, their concerns, and the associated risks. Findings indicate that AI is primarily used to search for information and references, assist with completing coursework, and support independent learning. The concerns and risks identified by students include over-reliance, decreased critical and creative thinking skills, and ethical and data security issues. These findings suggest that AI must be used wisely for educational purposes, addressing these risks. Educational policies related to AI use must be improved and strengthened to maximize AI's benefits, aiming to support ethical and integrated education.